2020
DOI: 10.21037/apm-20-44
|View full text |Cite
|
Sign up to set email alerts
|

Impact of honey on radiotherapy-induced oral mucositis in patients with head and neck cancer: a systematic review and meta-analysis

Abstract: Background: Oral mucositis is one of the most frequent, irreversible and distressing complications faced by head and neck cancer (HNC) patients undergoing radiotherapy. Several studies have investigated the role of honey in the prevention and alleviation of radiation-induced oral mucositis in HNC patients, however, a definitive conclusion has not yet been generated. We performed this updated systematic review and metaanalysis to determine whether honey can prevent and alleviate radiation-induced oral mucositis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(106 reference statements)
2
12
1
1
Order By: Relevance
“…Münstedt and Männle (2019) [73] in their review evaluating the use of honey as an OM treatment showed a decrease in the severity of the ulcers, which harmonized with the scientific articles found in the present paper and in the systematic review and meta-analysis conducted by Tian et al (2020) [74].…”
Section: Honeysupporting
confidence: 87%
See 1 more Smart Citation
“…Münstedt and Männle (2019) [73] in their review evaluating the use of honey as an OM treatment showed a decrease in the severity of the ulcers, which harmonized with the scientific articles found in the present paper and in the systematic review and meta-analysis conducted by Tian et al (2020) [74].…”
Section: Honeysupporting
confidence: 87%
“…Other aspects mentioned by Tian et al (2020) [74] include the indication of a potential decrease in the incidence of OM during the treatment with honey; however, from the present study, only one study proved significant prevention.…”
Section: Honeycontrasting
confidence: 64%
“… 42 MGH could reduce pain when used in other oral conditions in humans such as mucositis and tonsillectomy wounds, as reported in two meta-analyses. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…42 MGH could reduce pain when used in other oral conditions in humans such as mucositis and tonsillectomy wounds, as reported in two meta-analyses. 43,44 To investigate the underlying mechanism of how MGH improves intra-oral wound healing in more detail, future research may include additional possible objective outcome measures, such as inflammatory markers (systemically in the blood or locally in potential exudate), alveolar bone formation and microbiological colonisation. As these parameters are harder to evaluate, requiring extra blood sampling, CT and/or sedation, and these procedures result in increased discomfort, such investigations would require prior ethical approval.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the existing literature has focused on treatments after radiation injury has occurred, ranging from topical agents, such as honey, to more invasive measures, such as fat grafting. 8 9 10 Preventative modalities are poorly represented; the best studied measures are typically nonspecific interventions that are largely out of the surgeon's control, such as modulation of radiation doses and maintenance of good oral hygiene. 11 12 Few specific interventions are described, and even fewer are supported by a wide body of clinical evidence.…”
Section: Tablementioning
confidence: 99%